Imaginative Expression of Autistic Children's Painting as a Form of Response to The Environment at Fredofios School Yogyakarta - Yulaida, Ita; Triyanto, Triyanto; Sugiarto, Eko (Universitas Negeri Semarang, 2019)
Autistic children are children who experience impaired brain function development which is characterized by difficulties in the ability of social interaction, communication with the environment, behavior and a delay in the academic field. Imaginative expressions in children with autism can be done through the media of painting. The media of painting can help as a therapy and to develop the painting skills of autistic children. This study aims to review and analyze (1) The form of autistic children's painting in the Autistic Advanced School (SLA) Fredofios. (2) Environmental elements visualized in paintings as a result of the imagination of children with autism. The method used in this research is qualitative. Data is collected through controlled observations, interviews, and document studies. The data validity technique uses triangulation and interactive data analysis techniques. The results of this study First, the form of autistic children's painting shows artistic painting in terms of subjects, color elements and shapes. Second, visualized environmental elements describe the school environment and family environment. Expressions of imagination of autistic children are always inspired by the environment every day.